Structures of actomyosin crossbridges in relaxed and rigor muscle fibers. - Yu, L C (1989)
It was shown previously that a significant fraction of the myosin crossbridges is attached to actin in the skinned rabbit psoas fibers under relaxed conditions at low ionic strength and low temperature (Brenner, B., M. Schoenberg, J. M. Chalovich, L. E. Greene, and E. Eisenberg. 1982. Proc. Natl. Acad. Sci. USA. 79:7288-7291; Brenner, B., L. C. Lu, and R. J. Podolsky. 1984. Biophys. J. 46:299-306). In the present work, the structure of the attached crossbridges in the relaxed state between ionic strengths of 20 and 100 mM, as compared with that in the rigor state, is further examined by equatorial x-ray diffraction. Mass distributions projected along the fiber axis are reconstructed based on the first five equatorial reflections such that the spatial resolution is 128 A. The fraction of crossbridges attached under relaxed conditions are estimated to be in the range of 30% (at 100 mM ionic strength) and 60% (at 20 mM). The reconstructed density maps suggest that in the relaxed state, upon attachment the part of the crossbridge that centers around the thin filament is small, and the attachment does not significantly alter the center of mass of the myosin head distribution around the thick filament backbone. In contrast, accretion of mass in the rigor state occurs in a wider region surrounding the thin filament. In this case, mass in the surface region of the thick filament backbone is shifted slightly outward, probably by approximately 10 A. A schematic model for interpreting the present data is presented.